2023
DOI: 10.1039/d3nr00281k
|View full text |Cite
|
Sign up to set email alerts
|

Reconfigurable scaffolds for adaptive tissue regeneration

Abstract: Tissue engineering and regenerative medicine have offered promising alternatives for clinical treatments of body tissue traumas, losses, dysfunctions, or diseases, where scaffold-based strategies are particularly popular and effective. Over the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 145 publications
0
5
0
Order By: Relevance
“…As a result, the actin and morphology alignment of human fibroblasts were induced, suggesting that the anisotropic movement can instruct the cellular behavior in agreement to a previous study. [41] The novelty of the present study lies in the fact that the anisotropic movement of the abdomen was synchronized with BMR mesh under implantation, thereby suggesting a considerable solution to prevent hernia recurrence. This novelty was gen-erated by analyzing the influence of mesh patterns to support the movement and regeneration of abdominal tissue.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…As a result, the actin and morphology alignment of human fibroblasts were induced, suggesting that the anisotropic movement can instruct the cellular behavior in agreement to a previous study. [41] The novelty of the present study lies in the fact that the anisotropic movement of the abdomen was synchronized with BMR mesh under implantation, thereby suggesting a considerable solution to prevent hernia recurrence. This novelty was gen-erated by analyzing the influence of mesh patterns to support the movement and regeneration of abdominal tissue.…”
Section: Discussionmentioning
confidence: 95%
“…As a result, the actin and morphology alignment of human fibroblasts were induced, suggesting that the anisotropic movement can instruct the cellular behavior in agreement to a previous study. [ 41 ]…”
Section: Discussionmentioning
confidence: 99%
“…Recently, our group found that surface topographical cues could modulate cell affinity on demand. [119] Accordingly, a microelectrode array with micro-cone surface topographies has been designed and developed, [116] which could simultaneously enhance the formation of neural networks and inhibit the adhesion of astrocytes (Figure 13d), holding promises to address the cell affinity challenges of the implants for visual restoration.…”
Section: Interfacial Adaptionmentioning
confidence: 99%
“…[11] These distinctive features have positioned PEDOTs as an attractive candidate for the fabrication of biodegradable and electroconductive polymers, particularly in the field of tissue engineering (TE) scaffolds. [12][13][14][15][16][17] In general, TE scaffolds are designed to be nanoporous, electroconductive, and biodegradable structures that can provide temporary support for tissue. [18][19][20][21] However, a critical challenge lies in the fact that PEDOTs, along with many other CPs, exhibit low or non-biodegradability, brittleness, and insolubility.…”
Section: Introductionmentioning
confidence: 99%